2020
DOI: 10.2147/sccaa.s237686
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characterization and Immunomodulation of Canine Amniotic Membrane Stem Cells</p>

Abstract: Purpose: Amniotic membrane stem cells have a high capacity of proliferation, cell expansion, and plasticity, as well as immunomodulatory properties that contribute to maternal-fetal tolerance. Owing to the lack of research on human amniotic membrane at different gestational stages, the canine model is considered ideal because of its genetic and physiological similarities. We aimed to characterize the canine amniotic membrane (CAM) cell lineage in different gestational stages and evaluate the expression of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
8
1
Order By: Relevance
“…Colony formation was similar in both canine cell cultures. However, the mean number of colonies obtained in this study for AT and UC-MSCs is lower when compared with what found for canine amniotic membrane derived MSCs using the same protocol [ 23 ]. It is likely that different cells and culture medium influenced the results.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Colony formation was similar in both canine cell cultures. However, the mean number of colonies obtained in this study for AT and UC-MSCs is lower when compared with what found for canine amniotic membrane derived MSCs using the same protocol [ 23 ]. It is likely that different cells and culture medium influenced the results.…”
Section: Discussioncontrasting
confidence: 68%
“…found for canine amniotic membrane derived MSCs using the same protocol [23]. It is likely that different cells and culture medium influenced the results.…”
Section: Plos Onementioning
confidence: 92%
See 1 more Smart Citation
“…They are non-teratogenic [ 55 ], pluripotent, and also have regenerative properties and low immunogenicity [ 31 , 34 , 55 ]. Canine MSCs derived from the amniotic membrane have recently been isolated and proved to have the same characteristics, biosafety, and properties as other MSCs, which make them a good candidate for clinical trials [ 32 , 56 ]. The composition and potential use of cAMSC-CM have not been studied yet, but since CM contains cell paracrine factors [ 37 ], the application of cAMSC-CM in clinical studies seems to be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Since, interest in this tissue as a source of MSCs has also developed in dogs. As shown in Table 1 , canine AMMSCs expressed embryonic and MSCs markers, such as OCT4, CD44, CD184, and CD29 and could differentiate into neurocytes, osteocytes, adipocytes and chondrocytes based on cell morphology, specific stains, and molecular analysis [ 40 , 48 , 49 , 50 , 51 , 52 ]. Regarding the immunomodulatory properties of AMMSCs, Borghesi et al [ 51 ] found low MHC-I expression and no MHC-II expression, giving the MSCs the potential to escape recognition by CD4+T cells [ 55 ].…”
Section: Canine Mesenchymal Stem Cells From Foetal Adnexamentioning
confidence: 99%